Place time consistency and stroke rates required for success in K1 200-m sprint kayaking elite competition - McDonnell, L. K.; Hume, P. A.; Nolte, V. (International Journal of Performance Analysis in Sport, 2013)
The aim was to evaluate place time consistency, and identify stroke rate trends required for success in K1 200-m kayaking. Race times and videos for each place in the A-finals of twelve World Cup and five World Championship regattas held from 2006 to 2011 were collected from electronic databases. Quality broadcasted videos (24 Hz) of four men's and two women's World Championship K1 200-m races were retained for stroke rate analysis. Place time consistency was determined using a coefficient of variation (CV%). World Championship place time consistency was better (Men = 0.7 to 1.5%, Women = 0.7 to 1.7%) than World Cup place time consistency (Men = 2.7 to 6.9%, Women = 4.3 to 5.4%). World Championship medallists' place time consistency did not exceed 1% for males and females. After the initial acceleration phase, all World Championship medallists showed a decline in stroke rate throughout the race (slope = -0.2 to -1.3 spm/s). World Championship medallists' stroke rates averaged 158 ± 8.2 spm for males and 139 ± 5.8 spm for females. In conclusion, World Championship medal target times were consistent, and stroke rate and displacement ranges required to achieve these targets have been provided in a matrix.